Measuring the Attitude of Mainstream Educators towards having students with ADHD in their Classrooms in a private school in Dubai- A Case Study. - ABDULLAH, MARYAM (2023)
The United Arab Emirates (UAE) has put a lot of effort into ensuring that essential accommodations and adaptations to the curriculum and setting for learning are effectively offered and implemented in regular classrooms. Law number 26 was enacted as the first law to safeguard the rights of people of determination in 2006. The Ministry of Education introduced guidelines for the provisions to include students with needs in 2007. Furthermore, the Knowledge and Human Development Authority (KHDA) created a guide for schools in 2017, which includes crucial instructions for schools to adopt and implement high-quality inclusive educational standards for pupils of determination. A student's academic, social, and well-being may be profoundly impacted by ADHD, a neurodevelopmental disease characterized by behaviors such as inattention, hyperactivity, and impulsivity. Examining the experiences and difficulties faced by learners who have ADHD in traditional educational settings is critical given the rising incidence of ADHD in the world. In this aspect, teachers' attitudes are crucial when evaluating the success of inclusion and appropriate assistance for students with ADHD. This study assesses general education teachers' attitudes towards incorporating ADHD students in their regular classrooms and focuses on learning how teachers perceive including ADHD students in the usual classroom environment. Data was gathered using a mixed-methods approach in which semi-structured interviews were conducted after administering a questionnaire to the entire teaching team. Ten teachers from pre-primary, primary, and high school participated in the semi-structured interview. The results show that teachers' views on incorporating ADHD students in regular classes are subjective and based on their own experiences. Teachers can foster a friendly learning environment in the classroom by utilizing a variety of methods of instruction, providing support and motivation to students with ADHD followed by collaboration with the Special Education Needs (SEN) department. The implications of this study go beyond the setting of private schools. Similar school systems and authorities to improve their inclusive education practices for ADHD children can use these findings. Trying to create more inclusive and encouraging learning environments for everyone by understanding the particular needs of those children and putting the recommended adjustments into practice. Significant recommendations have been compiled to help mainstream teachers better understand how to incorporate students with ADHD as well as recommendations for additional study to contribute to the UAE perspective and other neurological illnesses. In conclusion, this research provides insightful information that will aid policymakers, administrators, and educators in promoting inclusive education and enhancing results for ADHD students.